Fournier′s gangrene of the penis - Francis Leo Tauro; M Roshan; B S Sathish Rao; J Ravikrishnan; Leo T Menezes (Indian Journal of Plastic Surgery)
Fournier′s gangrene is a rare, fulminant, though generally localized disease of the scrotum and penis with occasional extension up the abdominal wall. The usual organism is an anaerobic streptococcus synergistic with some second organism. Our case was unusual in that only the penis was involved without involving the scrotum or abdominal wall. Early therapy is the key, including hospitalization, debridement of entire shaft of the penis distal to the devasted area without excising the normal skin, parenteral broad-spectrum antibiotics & skin grafting. Only few cases of Fournier′s gangrene of the penis have been reported.